LIN28A expression reduces sickling of cultured human erythrocytes. - Jaira F de Vasconcellos; Ross M Fasano; Y Terry Lee; Megha Kaushal; Colleen Byrnes; Emily R Meier; Molly Anderson; Antoinette Rabel; Raul Braylan; David F Stroncek; Jeffery L Miller (PLoS ONE, 2014)
Induction of fetal hemoglobin (HbF) has therapeutic importance for patients with sickle cell disease (SCD) and the beta-thalassemias. It was recently reported that increased expression of LIN28 proteins or decreased expression of its target let-7 miRNAs enhances HbF levels in cultured primary human erythroblasts from adult healthy donors. Here LIN28A effects were studied further using erythrocytes cultured from peripheral blood progenitor cells of pediatric subjects with SCD. Transgenic expression of LIN28A was accomplished by lentiviral transduction in CD34(+) sickle cells cultivated ex vivo in serum-free medium. LIN28A over-expression (LIN28A-OE) increased HbF, reduced beta (sickle)-globin, and strongly suppressed all members of the let-7 family of miRNAs. LIN28A-OE did not affect erythroblast differentiation or prevent enucleation, but it significantly reduced or ameliorated the sickling morphologies of the enucleated erythrocytes.